STUDI PENGARUH CNG-RATIO PADA MOTOR DIESEL BERBAHAN BAKAR GANDA SOLAR-CNG - Widodo B. Santoso; Achmad Praptijanto (Department of Mechanical Engineering, University of Udayana, 2006)
Preliminay research to convert diesel engine to utilize natural gas as main fuel has been conducted. For that purpose, an air-cooled single cylinder stationary diesel engine was converted to operate in a dual fuel combustion with CNG as the main fuel and diesel fuel as a pilot fuel. Diesel fuel was injected a few degree before TDC. The test was running in three modes, i.e. rated power mode (3000 rpm), maximum torque mode (2000 rpm), and medium speed mode (2500 rpm). Cylinder pressure, rate of heat release, air consumption, CNG consumption and fuel consumption were investigated. The results show that the replacement of diesel fuel with CNG give a different effect on combustion for the three modes. Increased CNG-ratio up to 40% and 10% resulted in increasing average maximum cylinder pressure for maximum torque mode (2000 rpm) and medium speed mode (2500 rpm) respectively. On the other hand, increased CNG-ratio resulted in decreasing average maximum cylinder pressure for rated power mode (3000 rpm).